ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, INDEKS PEMBANGUNAN MANUSIA, DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP TINGKAT KEMISKINAN DI PROVINSI BANTEN PERIODE TAHUN 2016-2021 - Arya Cembawan Wijaksana (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
The poverty rate in Banten Province is still very high so that the level of welfare in society is still low and not evenly distributed, this is because many factors cause poverty such as Regional Gross Domestic Product, Human Development Index, and Open Unemployment Rate. This research was conducted with the aim of testing and analyzing the effect of the Gross Regional Domestic Product, the Human Development Index, and the Open Unemployment Rate on the Poverty Rate in Banten Province in the 2016-2021 period. This research is quantitative research. Using secondary data types obtained from BPS Banten Province and other supporting journal literature. In this study the method used was panel data method in the form of cross sections of 8 regencies/cities in Banten Province and time series data from 2016-2021 using the Eviews 9 program.